MINIMASI KONSUMSI ENERGI PADA PERMASALAHAN HYBRID FLOW SHOP SCHEDULING DENGAN ALGORITMA SALP SWARM - Bayu Nur Hidayat; Dana Marsetya Utama; Ikhlasul Amallynda (Jurnal Ilmiah Teknik Industri, 2023)
The scarcity and possible depletion of energy sources in the future is due to the high energy consumption in the manufacturing industry. One of the efforts to deal with this problem is scheduling. This article investigates the Hybrid Flow Shop Scheduling Problem (HFSSP) to minimize energy consumption. A metaheuristic algorithm procedure is proposed, inspired by the Salp swarm in the ocean, the Salp Swarm Algorithm. The SSA algorithm is proposed to determine the optimal sequencing considering minimal energy consumption. An interesting finding of this study is that the higher the population and iterations, the lower the energy consumption. In addition, the optimization results show that the total energy consumption is due to variations in setup and removal energy consumption and idle machine energy consumption. From the numerical results, the SSA algorithm can produce scheduling with minimal energy consumption compared to the heuristic procedure.